PENGARUH KUALITAS LAYANAN TERHADAP KEPATUHAN MEMBAYAR WAJIB PAJAK (STUDI KASUS DI KANTOR PELAYANAN PAJAK DI JAKARTA KELAPA GADING) - Yeyen Rumi NuroctaViani; Y. Agus Bagus Budi N (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2012)
Compliance in every single state is crucial issue. Indonesia, as a country of more than 240 million people must consider this as a locomotive factor to attract higher participation from people. But compliance is rather a sociological term, since it is related with certain factors such as reliability, responsiveness, assurance, empathy, tangible and other factors. This study explained the influencing factors toward compliance. Compliance in this study, reflected into two items which are tax payment and tax filling (monthly or annually). Quality services provided by tax account representative and all element from the tax office are core elements needed by taxpayers. Poor quality services will result poor participation from taxpayers.